King and MaxwellL Sean King & Michelle Maxwell #6 - Baldacci, David (New York : Grand Central Publishing, 2013)
"Sean King and Michelle Maxwell return in the latest blockbuster thriller from #1 New York Times bestselling author David Baldacci. Watch King & Maxwell, TNT's new series based on David Baldacci's blockbuster novels, on Mondays at 10 p.m. (ET/PT) "--.
Keywords: King, Sean (Fictitious character) -- Fiction; Maxwell, Michelle (Fictitious character) -- Fiction; Private investigators -- Fiction; Security, International -- Fiction; FICTION / Thrillers; Suspense fiction